Novel Targets and Therapeutic Strategies to Protect Against Hepatic Ischemia Reperfusion Injury - Mao, Xin-li; Cai, Yue; Chen, Ya-hong; Wang, Yi; Jiang, Xiu-xiu; Ye, Li-ping; Li, Shao-wei (Frontiers in Medicine, 2022)
Hepatic ischemia reperfusion injury (IRI), a fascinating topic that has drawn a lot of interest in the last few years, is a major complication caused by a variety of clinical situations, such as liver transplantation, severe trauma, vascular surgery, and hemorrhagic shock. The IRI process involves a series of complex events, including mitochondrial deenergization, metabolic acidosis, adenosine-5’-triphosphate depletion, Kupffer cell activation, calcium overload, oxidative stress, and the upregulation of pro-inflammatory cytokine signal transduction. A number of protective strategies have been reported to ameliorate IRI, including pharmacological therapy, ischemic pre-conditioning, ischemic post-conditioning, and machine reperfusion. However, most of these strategies are only at the stage of animal model research at present, and the potential mechanisms and exact therapeutic targets have yet to be clarified. IRI remains a main cause of postoperative liver dysfunction, often leading to postoperative morbidity or even mortality. Very recently, it was reported that the activation of peroxisome proliferator-activated receptor γ (PPARγ), a member of a superfamily of nuclear transcription factors activated by agonists, can attenuate IRI in the liver, and FAM3A has been confirmed to mediate the protective effect of PPARγ in hepatic IRI. In addition, non-coding RNAs, like LncRNAs and miRNAs, have also been reported to play a pivotal role in the liver IRI process. In this review, we presented an overview of the latest advances of treatment strategies and proposed potential mechanisms behind liver IRI. We also highlighted the role of several important molecules (PPARγ, FAM3A, and non-coding RNAs) in protecting against hepatic IRI. Only after achieving a comprehensive understanding of potential mechanisms and targets behind IRI can we effectively ameliorate IRI in the liver and achieve better therapeutic effects.